2015
DOI: 10.1002/etc.3202
|View full text |Cite
|
Sign up to set email alerts
|

Textile dyes induce toxicity on zebrafish early life stages

Abstract: Textile manufacturing is one of the most polluting industrial sectors because of the release of potentially toxic compounds, such as synthetic dyes, into the environment. Depending on the class of the dyes, their loss in wastewaters can range from 2% to 50% of the original dye concentration. Consequently, uncontrolled use of such dyes can negatively affect human health and the ecological balance. The present study assessed the toxicity of the textile dyes Direct Black 38 (DB38), Reactive Blue 15 (RB15), Reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 37 publications
0
34
0
2
Order By: Relevance
“…Azo dyes [Maguire, 1992;Umbuzeiro et al, 2005b;Carneiro et al, 2010;Zocolo et al, 2015] and aromatic amines [Ohe et al, 1999;Oliveira et al, 2007] have been found in aquatic ecosystems, and data on acute and chronic toxicity in aquatic organisms show possible effects on fitness endpoints such as survival, reproduction, and growth [Novotn y et al, 2006;Bae and Freeman, 2007;Liu et al, 2007;Immich et al, 2009;Ferraz et al, 2011;Vacchi et al, 2013;Luna et al, 2014]. However, studies in aquatic organisms dealing with the genotoxic potency of environmental samples containing azo dyes and aromatic amines are still scarce [Al-Sabti, 2000;Cavaş and Ergene-G€ oz€ ukara, 2003;Zhang et al, 2014], despite the fact that such compounds in their pure or commercial form have proved to be genotoxic and mutagenic in bacteria and mammalian cells [Oliveira et al, 2007[Oliveira et al, , 2006Chequer et al, 2009Chequer et al, , 2011Ferraz et al, 2011;de Oliveira et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Azo dyes [Maguire, 1992;Umbuzeiro et al, 2005b;Carneiro et al, 2010;Zocolo et al, 2015] and aromatic amines [Ohe et al, 1999;Oliveira et al, 2007] have been found in aquatic ecosystems, and data on acute and chronic toxicity in aquatic organisms show possible effects on fitness endpoints such as survival, reproduction, and growth [Novotn y et al, 2006;Bae and Freeman, 2007;Liu et al, 2007;Immich et al, 2009;Ferraz et al, 2011;Vacchi et al, 2013;Luna et al, 2014]. However, studies in aquatic organisms dealing with the genotoxic potency of environmental samples containing azo dyes and aromatic amines are still scarce [Al-Sabti, 2000;Cavaş and Ergene-G€ oz€ ukara, 2003;Zhang et al, 2014], despite the fact that such compounds in their pure or commercial form have proved to be genotoxic and mutagenic in bacteria and mammalian cells [Oliveira et al, 2007[Oliveira et al, , 2006Chequer et al, 2009Chequer et al, , 2011Ferraz et al, 2011;de Oliveira et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…The most common problem associated with reactive dyes is that large fractions of these dyes (10–30%) are wasted during the dyeing processes as they get discharged along with the textile wastewater; up to 0.6–0.8 g dye dm −3 can be detected in dyestuff effluents . Discharging dyes into the ecosystem reduces light penetration in aquatic systems and could induce toxicity in biotic communities, especially aquatic communities , besides causing visually displeasing habitats. Thus, there is a necessity to decolorize textile wastewaters before they are discharged into the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Para as caracterizações dos tecidos por difração de raios X (DRX), microscopia eletrônica de varredura (MEV) e análise termogravimétrica (TGA) foi selecionada a amostra têxtil S02-4, a qual apresentou um maior FPU. A funcionalização dos tecidos de algodão com as NPs de ZnO foi através do processo de tingimento têxtil de esgotamento e segundo a pesquisa realizada por Oliveira et al (2016), a quantidade de corante que se perde diretamente nas águas residuais de um processo de tingimento têxtil, depende do tipo de corante, esta quantidade oscila entre 2% a 50% da concentração inicial do corante (OLIVEIRA et al, 2016). Com base nesta pesquisa e assumindo para nosso caso, que o ZnO representa um tipo de corante, poderíamos atribuir que o 27% restante da quantidade de NPs de ZnO se perde nas águas residuais do banho de esgotamento, banho de neutralização e enxague.…”
Section: Caracterizações Dos Tecidos Funcionalizados Com Nanopartículunclassified